2018
DOI: 10.1042/bsr20180580
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-X-C motif) ligand 1 is associated with tumor progression and poor prognosis in patients with colorectal cancer

Abstract: Chemokine (C-X-C motif) ligand 1 (CXCL1) is a chemotactic cytokine known to regulate cancer progression and invasion. However, the prognostic significance of CXCL1 expression in colorectal cancer (CRC) has not been fully characterized. The present study explored the clinicopathological significance and potential role of CXCL1 in the carcinogenesis and progression of CRC. The protein expression of CXCL1 was measured immunohistochemically in tissue microarrays constructed from 276 CRC patients. CXCL1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 24 publications
4
49
1
Order By: Relevance
“…Clinically, the tissue microarray analysis of 276 patients with colon cancer indicated that CXCL1 played a vital role in the progression and metastasis of colon cancer [44]. The expression level of CXCL1 is an independent prognostic factor for both OS and DFS in patients with colon cancer [45]. Therefore, disrupting the TAMs/CXCL1 signaling to block PMN formation is emerging as a promising therapeutic approach for cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the tissue microarray analysis of 276 patients with colon cancer indicated that CXCL1 played a vital role in the progression and metastasis of colon cancer [44]. The expression level of CXCL1 is an independent prognostic factor for both OS and DFS in patients with colon cancer [45]. Therefore, disrupting the TAMs/CXCL1 signaling to block PMN formation is emerging as a promising therapeutic approach for cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1 has been reported to play an important role in CRC progression and metastasis by inducing glycolysis [179]. CXCL1 is also an ELR + CXC chemokine that induces angiogenesis by binding to CXCR2 [109].…”
Section: Cxcl1mentioning
confidence: 99%
“…An accumulating number of evidence shows that chemokines are frequently expressed in various tumours to regulate tumour cells function in both physiological and pathological conditions [2,3]. In terms of CRC, several chemokines are highly expressed in tumour tissue and cell line, like CXCL1 [4], CXCL8 [5], CXCL10 [6] and CCL20 [7]. Functional assays demonstrated that CXCL8 and CCL20 co-stimulation led to the increase of CRC cells proliferation and migration [8,9].…”
Section: Introductionmentioning
confidence: 99%